2009
DOI: 10.1088/0031-8949/79/02/025702
|View full text |Cite
|
Sign up to set email alerts
|

Wall thickness of single-walled carbon nanotubes and its Young's modulus

Abstract: Young's modulus of single-walled carbon nanotubes (SWCNTs) was calculated by a modern pseudo-potential ab initio method. Using different models for wall thickness, we found that the Young's modulus of an SWCNT varies in a wide range from 0.94 to 5.81 TPa. Here, an SWCNT's wall thickness was obtained by electronic structure calculation. Using the wall thickness, we obtained that the Young's modulus of an SWCNT is 1.06-1.16 TPa, which is in agreement with the experimental result of 1.20-1.25 TPa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…Similar observations hold for an orthorhombic crystal. From the Table III data, it is observed that for Ni/CNT composites, the c ii ͑i =1-6͒, c 11 + c 22 −2c 12 , c 22 + c 33 −2c 23 , c 11 + c 33 −2c 13 , and c 11 + c 22 + c 33 +2c 12 +2c 23 +2c 13 are all positive, and thus it can be reasonably concluded that Ni/CNTs composites are mechanically stable. This is an encouraging result for the fabrication of nanocomposite materials by embedding the CNTs in metal matrices.…”
Section: Single-crystal Elastic Constantsmentioning
confidence: 83%
See 4 more Smart Citations
“…Similar observations hold for an orthorhombic crystal. From the Table III data, it is observed that for Ni/CNT composites, the c ii ͑i =1-6͒, c 11 + c 22 −2c 12 , c 22 + c 33 −2c 23 , c 11 + c 33 −2c 13 , and c 11 + c 22 + c 33 +2c 12 +2c 23 +2c 13 are all positive, and thus it can be reasonably concluded that Ni/CNTs composites are mechanically stable. This is an encouraging result for the fabrication of nanocomposite materials by embedding the CNTs in metal matrices.…”
Section: Single-crystal Elastic Constantsmentioning
confidence: 83%
“…For the composites with the MWCNT, c 12 and c 13 decrease for both low and high CNT volume fractions. For c 23 , however, a small increase is seen for both volume fractions. The values of c 44 , c 55 , and c 66 decrease in the composites compared to pure Ni ͑125 GPa͒ and depend on the CNT concentration in the composites.…”
Section: Single-crystal Elastic Constantsmentioning
confidence: 85%
See 3 more Smart Citations